Pulmonary infections in the returned traveller. Issue 1 (December 2017) - Trimble, Ashleigh; Moffat, V.; Collins, A.
Abstract Pulmonary infections in the returned traveller are a common presentation. A wide variety of infections may present with pulmonary symptoms. It is important for clinicians to differentiate the cause of these symptoms. The risk of contracting certain travel-related pulmonary diseases depends on travel destination, length of stay, activities undertaken and co-morbidities. Some pathogens are found worldwide, whilst others are related to specific locations. This review article will discuss the approach to diagnosing and treating pulmonary infections in the returned traveller.